BRISP, a new small-angle time-of-flight neutron spectrometer to study collective dynamics in disordered matter - Orecchini, A.; Pilgrim, W.-C.; Petrillo, C.; Suck, J.-B.; Sacchetti, F. (Condensed Matter Physics, 2008)
An outline is given of the new neutron Brillouin Spectrometer BRISP which was installed during the last years
and recently became fully operational at the Institute Laue-Langevin in Grenoble (France). The main technical
features are described and some of the first experimental results are presented, demonstrating the present
capabilities of this new-type inelastic small-angle spectrometer. Future upgrades are foreseen and expected
to further improve the instrument performances. Подано короткий опис нового нейтронного брiлюенiвського спектрометра BRISP, що iнсталювався протягом останнiх рокiв та недавно почав дiяти в Iнститутi Лауе-Ланжевена у Ґреноблi (Францiя). Описано основнi технiчнi особливостi та представлено деякi першi експериментальнi результати, що демонструють наявнi можливостi цього малокутового непружнього спектрометра нового типу. В майбутньому передбачаються та очiкуються вдосконалення для майбутнього покращення роботи iнструмента.